2022
DOI: 10.3390/jcdd9120409
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Hub Genes in the Remodeling of Non-Infarcted Myocardium Following Acute Myocardial Infarction

Abstract: (1) Background: There are few diagnostic and therapeutic targets for myocardial remodeling in the salvageable non-infarcted myocardium. (2) Methods: Hub genes were identified through comprehensive bioinformatics analysis (GSE775, GSE19322, and GSE110209 from the gene expression omnibus (GEO) database) and the biological functions of hub genes were examined by gene ontology (GO) functional enrichment and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment. Furthermore, the differential expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 100 publications
(106 reference statements)
0
0
0
Order By: Relevance
“…14,15 Moreover, the gene set of immune cells after myocardial infarction has been extensively studied for the diagnosis and prediction of myocardial infarction. [16][17][18][19] Recently, a series of novel inflammatory factors, such as IL-36, IL-37 and IL-38, were identified here. 20 Current studies have confirmed that these novel inflammatory factors are closely associated with the progression of atherosclerosis.…”
Section: Introductionmentioning
confidence: 97%
“…14,15 Moreover, the gene set of immune cells after myocardial infarction has been extensively studied for the diagnosis and prediction of myocardial infarction. [16][17][18][19] Recently, a series of novel inflammatory factors, such as IL-36, IL-37 and IL-38, were identified here. 20 Current studies have confirmed that these novel inflammatory factors are closely associated with the progression of atherosclerosis.…”
Section: Introductionmentioning
confidence: 97%